PERANCANGAN APLIKASI INVENTORY BARANG BERBASIS WEB DENGAN METODE ECONOMIC ORDER QUANTITY (Studi Kasus : Elfiza Cell) - Henriyana; Maulana Ardiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Elfiza Celluler is a shop engaged in the sale and purchase of used mobile phones, quota vouchers, mobile phone accessories and computer accessories which is located at Jalan Kampung Masjid RT.03, RW.07, Mekarwangi Village, Tanah Sereal District, Bogor City. However, the rapid development of inventory technology at this time has made many stores, especially Elfiza Cellular, begin to develop a goods inventory system by creating a web-based inventory application. However, Elfiza Cellular does not yet have a computerized goods inventory system or a web-based goods inventory application. With this web-based goods inventory application, it is hoped that it can be a solution to problems that exist at Elfiza Cellular in managing store data such as: incoming goods data, outgoing goods data, goods requests, goods returns, supplier data, goods stock report data, and can determine the number of orders of goods efficiently.